Infectious mononucleosis complicated by acute haemolytic anaemia with a positive Donath-Landsteiner reaction - Wishart, M. M. (1973)
A patient with infectious mononucleosis complicated by acute haemolytic anaemia is described. The patient had, in addition to non-specific cold agglutinins in the serum, a positive Donath-Landsteiner reaction in the absence of syphilis. The association of a positive Donath-Landsteiner reaction with haemolytic anaemia in infectious mononucleosis has been described only once before.